Factors influencing the adoption of mobile banking among Generation Y - Adilah, Othman (2014)
The main purpose of this study is to examine what are the most significant factors that influence the intention to adopt Mobile Banking Services by Generation Y. This study was carried out among the respondents of the students at Universiti Utara Malaysia which includes three educational levels. In this study, a total of 400 questionnaire forms were distributed to respondents, but only 382 were returned. The variables that have been tested in this study were Perceived Usefulness, Perceive Ease of Use, Awareness, Trust, Perceived Value and Social Norms. The findings of the study revealed that all independent variables have a positive relationship with the dependent variable. Meanwhile, Social Norms have a positive influence towards Mobile Banking Adoption among Generation Y.